Factors Affecting Temporal and Spatial Variations of Microcystins in Gonghu Bay of Lake Taihu, with Potential Risk of Microcystin Contamination to Human Health - Qing Wang; Yuan Niu; Ping Xie; Jun Chen; Zhimei Ma; Min Tao; Min Qi; Laiyan Wu; Longgen Guo (The Scientific World Journal)
A field survey of the seasonal variation of microcystin (MC) concentration was performed in Gonghu Bay (a total of 15 sampling sites) of Lake Taihu from January to December 2008. Microcystis spp. biomass and intra-/extracellular MCs were significantly correlated with water temperature, suggesting the importance of temperature in cyanobacterial blooming in the lake. Higher MC concentration was found in summer and autumn, and peaks of Microcystis biomass and intra-/extracellular MC concentrations were all present in October. Spatially, risk of MCs was higher in littoral zones than in the pelagic area. There were significant correlations between N or P concentrations, and Microcystis biomass or MC content, suggesting that N and P levels affected MC production through influencing Microcystis biomass. Intra-/extracellular MCs and Microcystis biomass had negative exponential relationships with TN:TP, and the maximum values all occurred when TN:TP was <25. Multivariate analyses by pcca indicated that intra- and extracellular MC concentrations had better correlations with biological factors (such as Microcystis biomass and chl-a) than physicochemical factors. The maximum concentration reached up to 17 µg/L MC-Lreq, considerably higher drinking water safety standard (1 µg/L) recommended who. So it is necessary take measures reduce exposure risk of cyanobacterial toxins human beings.